1 - Editorial - Unterhalter, Elaine; Allais, Stephanie (Journal of Higher Education in Africa, 2022)
This special issue of the Journal of Higher Education in Africa examines global debates concerned with higher education as a public good, in the context of the lived realities, political and economic constraints as well as opportunities in contemporary Africa. While the articles draw on research and analysis conducted from 2017 to 2019, and were completed before the seismic changes associated with the COVID pandemic, the framing ideas regarding a contextualised understanding of the relationship between higher education and the public good are highly resonant with the processes of the COVID conjuncture. In this Editorial, we distil the key ideas that have shaped this collection of works, describe the research study that connected them, and draw out some of the implications of the findings for thinking about higher education and the public good in the light of the major disruptions of 2020–2021 for higher education in many African countries.